THE EFFECT OF SERVICES QUALITY ON SATISFACTION OF VISITORS TOURISM IN RECREATION PARK MUTUN BEACH LAMPUNG - Selfia Alkemega (International Conference On Law, Business and Governance (ICon-LBG), 2016)
Tourism is a product or service with an expectation that consumers can come to visit and be able to enjoy the attractions offered by the service provider company. In order to attract visitors, the manager should be able to provide the best quality service to create a satisfaction for consumers.The study population was visitors Mutun Beach Recreation Park Lampung. The sample was 400 respondents, and the sampling technique is accidental sampling. Data were collected by questionnaire. Analysis of data uses multiple linear regression analysis. The results of descriptive study showed that direct evidence of service quality (tangibles), reliability, responsiveness, assurance and empathy were included in good category. The results of the analysis obtained multiple regression Y = 11.55 + 0,257X1 + 0,239X2 0,445X3 + + + 0,235X5 0,241X4.The test results simultaneously obtained Fcount 22.469 with p value 0,000 <0,05. Partial test results obtained an influence on visitor satisfaction of Mutun Beach Recreation Park Lampung for variable direct evidence (responsiveness) of 2.5%, variable reliability of 1.25%, variable responsiveness 7.13%, variable guarantees (assurance) of 1.3%, and variable empathy of 1.14%.The results of the adjusted coefficient of determination (Adjusted R Square) is 0.212. It means that 21.2% of visitor satisfaction is influenced by the quality of service that includes direct evidence (tangibles), reliability, responsiveness, assurance, and empathy and the remaining 78.8% is influenced by other variables outside variables studied.The conclusion of the research is there is a significant influence of direct evidence (tangibles), reliability, responsiveness, assurance, and empathy partially or simultaneously.